THE EFFECT OF MILLING ON PARTICLE SIZE AND CRYSTAL STRUCTURE IN MECHANOCHEMICAL PROCESSING OF LEAD-CONTAMINATED SYNTHETIC SOIL - Lagowa, Muhammad Ikrar; Maulana, Lucky Zaehir (JOURNAL ONLINE OF PHYSICS, 2025)
crystal structure, which can immobilize lead and mitigate environmental contamination. Milling as a mechanical treatment plays a critical role in determining the final properties of the processed material. This study investigates the role of particle size and crystal structure in the mechanochemical treatment of lead-contaminated synthetic soil. Two synthetic soil samples were prepared in the laboratory, including lead contamination. Milling of the contaminated soils was carried out in a planetary ball mill. The samples were analysed using a lasersizer and X-Ray Diffraction (XRD) to investigate the change in particle size and identify the crystalline phase after milling. The results showed that milling initially reduced particle size, but further milling resulted in particle agglomeration, which was reflected by partial amorphization in soil samples after milling. Other than the partial amorphization, no phase change was detected in the crystal structure. In conclusion, milling resulted in the change of particle size but did not affect the crystalline phase of the milled sample, despite of partial amorphization.